LIVER TRANSPLANTATION IN CHILDREN: SIX-YEAR EXPERIENCE ANALYSIS - S. V. Gautier; O. M. Tsiroulnikova; Y. G. Moysyuk; D. G. Akhaladze; I. E. Tsiroulnikova; O. V. Silina; Kh. M. Khizroev; A. R. Monakhov; E. V. Chekletsova; V. A. Pets; V. N. Poptsov (Вестник трансплантологии и искусственных органов)
Introduction. Over the past few decades in Russia and other countries there has been signifi cant progress in the development of liver transplantation in children. It became possible to operate recipients with very low body mass, to perform transplant from cadaveric and living donors with incompatible blood type, as well as to perform single-step transplantation of liver with kidney or pancreas in patients with combined diseases.Aim: to investigate the 6-year experience of liver transplantation in children in V.I. Shumakov Federal Research Center of Transplantology and Artifi cial Organs.Materials and methods. From May 2008 to June 2014 304 liver transplantswere performed in 297 children aged from 3 months to 17 years with body mass 4 to 32 kg. 241 living donor liver left lateral section transplants (including 2 in conjunction with kidney), 8 left lobe (including 1 in conjunction with kidney), 40 right lobe liver transplants (including 1 in conjunction with kidney), and 9 cadaveric whole liver transplants (including 1 case of simultaneous liver and pancreas transplantation) and 6 split liver transplants (4 – split left lateral section transplantations and 2 extended right lobe liver grafts) were achieved.41 of these patients received a graft from AB0 – incompatible donors.Results. A retrospective evaluation of surgical technique and analysis of results were carried out. Early mortality was 8.1%, 1-year survival rate – 86.4%, 5-year survival rate – 78.8%.Conclusion. These results suggest the prospects of this procedure for pediatrictransplantation and require further investigation and promotion approaches in medical and social public.